The carboxylic acid transporters Jen1 and Jen2 affect the architecture and fluconazole susceptibility of Candida albicans biofilm in the presence of lactate - Alves, Rosana (2019)
Candida albicans has the ability to adapt to different host niches, often glucose-limited but rich in alternative carbon sources. In these glucose-poor microenvironments, this pathogen expresses JEN1 and JEN2 genes, encoding carboxylate transporters, which are important in the early stages of infection. This work investigated how host microenvironments, in particular acidic containing lactic acid, affect C. albicans biofilm formation and antifungal drug resistance. Multiple components of the extracellular matrix were also analysed, including their impact on antifungal drug resistance, and the involvement of both Jen1 and Jen2 in this process. The results show that growth on lactate affects biofilm formation, morphology and susceptibility to fluconazole and that both Jen1 and Jen2 might play a role in these processes. These results support the view that the adaptation of Candida cells to the carbon source present in the host niches affects their pathogenicity.